Effect of Shin'iseihaito on murine allergic reaction induced by nasal sensitization - Minami, Masaaki (J Tradit Complement Med, 2015)
Shin'iseihaito (Magnolia Flower Lung-Clearing Decoction; 辛夷清肺湯 xīn yí qīng fèi tāng), a formula of traditional Japanese kampo medicine (日本漢醫 rì běn hàn yī) and traditional Chinese medicine (TCM; 中醫 zhōng yī), has been used for the treatment of chronic sinusitis. The objective of this study was to evaluate the anti-allergic effect of shin'iseihaito on murine allergic reaction induced by nasal sensitization using ovalbumin (OVA) as an antigen. Extract of shin'iseihaito (SSHT) could reduce the eosinophil, serum IgE and interleukin (IL)-4 levels, while increased the interferon (IFN)-γ levels in allergic mouse. Furthermore, allergic-murine serum treated with SSHT could not activate passive cutaneous anaphylaxis (PCA) reaction in murine model. Thus, our study showed that SSHT may possess anti-allergic activity. We suggested that SSHT may contribute to inhibit the exacerbation of allergic reaction induced by nasal sensitization.